Hubungan Striae Gravidarum dengan Tingkat Kecemasan pada Ibu Hamil - Ricda Nurhikmayanti Hamzah; Sitti Nurjannah; Sulfiana; Mughni Wahdaniyah; Asrida (Sekolah Tinggi Ilmu Kesehatan Stella Maris Makassar, 2026)
Pregnancy is a physiological process involving various physical and psychological changes in women. One common physical change is striae gravidarum, which may affect body image and contribute to anxiety among pregnant women (Lestari & Rahmawati, 2020). This study aimed to determine the relationship between striae gravidarum and anxiety levels among pregnant women at Puskesmas Mootilango in 2026. This study employed an analytical observational design with a cross-sectional approach. A total of 68 pregnant women were selected using a purposive sampling technique. Data were collected using observation sheets and structured questionnaires and were analyzed using the Chi-Square test. The results showed that pregnant women without striae gravidarum were mostly not anxious (44.4%). In the mild striae gravidarum group, most respondents experienced mild anxiety (40.0%), while in the moderate striae gravidarum group, most respondents experienced moderate anxiety (44.4%). Meanwhile, most respondents in the severe striae gravidarum group experienced severe anxiety (75.0%). The Chi-Square test showed a p-value of < 0.001, indicating a significant relationship between striae gravidarum and anxiety levels among pregnant women. In conclusion, more severe striae gravidarum was associated with higher anxiety levels among pregnant women. Therefore, healthcare providers are expected to provide education and psychological support during pregnancy.